Effect of dichromate on population and growth of various protozoa isolated from industrial effluents - Haq, R U; Rehman, A; Shakoori, A R (Folia microbiologica, 2000)
Three protozoa belonging to genera Euglena, Vorticella and Stylonychia collected from industrial wastes were cultured in a medium containing inorganic salts, basically meant for the growth of algae. Protozoa showed rapid growth in the medium. Hexavalent chromium (K2Cr2O7) at a concentration of 5 micrograms/L in the medium adversely affected the growth of protozoa. At the end of eight days of Cr administration, the population of Euglena, Vorticella and Stylonychia increased 8-, 4.5- and 10-fold, respectively, as against 30-, 6.75- and 50-fold increase in the control cultures. No apparent death phase and no change in activity or morphology of protozoa was observed at this Cr concentration. The protozoa were also exposed to different metal ions, viz. Pb (2.42 mmol/L), Cr (0.48 mmol/L), Cd (0.36 mmol/L), administered in the culture medium for a period of 2 years. The metal tolerance for S. mytilus and V. microstoma was Pb > Cr > Cd. E. proxima could not tolerate any of the long-term metal treatments. Because of the ability of these protozoa to tolerate high concentrations of heavy metals, their potential role in remediation of heavy metals from industrial wastewater is considered.
Keywords: znečištění vody; Potassium Dichromate; Industrial Waste; Water Pollution; zvířata; Culture Media; dvojchroman draselný; Metals, Heavy; voda; Animals; kultivační média; Water; těžké kovy; průmyslový odpad; Eukaryota